1984
DOI: 10.1210/jcem-59-2-187
|View full text |Cite
|
Sign up to set email alerts
|

Ia+ T Cells in New Onset Graves' Disease*

Abstract: The Ia (immune-associated, DR) antigen is a cell surface glycoprotein which is absent on normal circulating T lymphocytes but present on activated T lymphocytes. We studied the expression of this antigen on circulating T lymphocytes from patients with untreated hyperthyroid Graves' disease. All patients (n = 33) with recent onset hyperthyroid Graves' disease studied had an increased percentage and number of circulating Ia+ T cells. Patients with non-Graves's hyperthyroidism or Graves' disease patients more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…In keeping with several studies focussing on increased HLA-DR expression (18)(19)(20)(21) we observed a significant increment vs healthy subjects for CD25 expression on peripheral CD4+ helper T cells in patients with newly diagnosed AH (441.4%), but not in GD. The mean CD25+CD45RA+ proportion of CD4+ cells was increased in both disease groups (GD, 17.6%; AH, 17.0%) vs healthy individuals (7.9%), but no difference was seen in patients with Graves' ophtalmopathy with respect to CD25 expression when compared to patients lacking eye disease.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In keeping with several studies focussing on increased HLA-DR expression (18)(19)(20)(21) we observed a significant increment vs healthy subjects for CD25 expression on peripheral CD4+ helper T cells in patients with newly diagnosed AH (441.4%), but not in GD. The mean CD25+CD45RA+ proportion of CD4+ cells was increased in both disease groups (GD, 17.6%; AH, 17.0%) vs healthy individuals (7.9%), but no difference was seen in patients with Graves' ophtalmopathy with respect to CD25 expression when compared to patients lacking eye disease.…”
Section: Discussionsupporting
confidence: 90%
“…Increased numbers of circulating HLA-DR+ T cells are seen almost exclusively restricted to the memory (antigen primed) in peripheral blood lymphocytes of patients with AITD of re-CD4+ T cell subset (8)(9)(10), it does not permit discrimination cent onset (18)(19)(20)(21), while the CD25 structure was not found to 'Division of Endocrinology and Metabolism, 3rd Department of Medicine, institute of General and Experimental Pathology, and 'Department of Urology, University of Vienna, Vienna, Austria. 117 be increased (22,23).…”
Section: Expression In Normal Individuals Ismentioning
confidence: 99%
“…Although potential free-binding sites on the FITC-labelled second antibody were not blocked for double stain¬ ing there was no evidence of spurious binding of the Leu 2a or Leu 3a phycoerythrin conjugated antibodies based on 1. concurrent staining with OKT3 (against CD3; all T cells within ±5% of the sum of the Leu 2a plus Leu 3a populations of double stained cells); 2. the total numbers of Leu 2a plus 3a stained cells showed no significant dif¬ ference when double staining was done with anti-DRl or Tal, which used the anti-mouse IgG-FITC, compared with V. villosa binding which did not, and 3. control values for DR+T cells agreed with previously published normal values (11)(12)(13).…”
Section: T Cell Subsetssupporting
confidence: 90%
“…Their data were conflicting, but it was generally believed that percentages of circulating CD3+ and CD4+ T cells in peripheral blood in patients with Graves' disease were similar to those in normal controls [12,13]. In contrast, the percentage of circulating CD8+ cells was lower and that of HLA-DR+ cells was higher in patients with Graves' disease than those in normal controls [12][13][14]. Since then, the percentage of activated T cell subsets in patients with autoimmune thyroid diseases has been reported, using two-color dye labeling and dual laser activated cell sorter analysis [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%